Spheroid-Derived Cells From Renal Adenocarcinoma Have Low Telomerase Activity and High Stem-Like and Invasive Characteristics - Saeednejad Zanjani, Leili; Madjd, Zahra; Rasti, Arezoo; Asgari, Mojgan; Abolhasani, Maryam; Tam, Kevin J.; Roudi, Raheleh; Mælandsmo, Gunhild Mari; Fodstad, Øystein; Andersson, Yvonne (Frontiers in Oncology, 2019)
Abstract Cancer stem cells (CSCs) are a theorized small subpopulation of cells within the tumors thought to be responsible for metastasis, tumor development, disease progression, treatment-resistance, and recurrence. Therefore, the identification, isolation, and biological characterization of CSCs may facilitate the development of efficient therapeutic strategies targeting CSCs. This study aims to compare the biology and telomerase activity of CSCs to parental cells (PCs) in renal cancer. Renal CSCs were enriched from the ACHN cell line using a sphere culture system. Spheroid-derived cells (SDCs) and their adherent counterparts were compared with respect to their colony and sphere formation, expression of putative CSC markers, tumorigenicity in non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice, and invasiveness. The expression of genes associated with CSCs, stemness, EMT, apoptosis, and ABC transporters was also compared between the two populations using quantitative real-time PCR (qRT-PCR). Finally, telomerase activity, hTERT expression, and sensitivity to MST-312, a telomerase inhibitor, was investigated between the two populations. We demonstrated that a subpopulation of ACHN cells were capable of growing as spheroids with many properties similar to CSCs including higher clonogenicity, superior colony- and sphere-forming ability, stronger tumorigenicity and invasiveness. In addition, SDCs demonstrated higher expression of markers for CSCs, stemness, EMT, apoptosis, and ABC transporter genes compared to PCs. The expression of hTERT and telomerase activity in SDCs was significantly lower than PCs, however, the SDC population was more sensitive to MST-312 compared to PCs. These findings indicate that the SDC population exhibits stem-like potential and invasive characteristics. Moreover, reduced expression of hTERT and telomerase activity in SDCs demonstrate that the expression of hTERT and telomerase activity are not always higher in CSCs. Our results also show that MST-312 treatment inhibits SDCs more strongly than PCs and may therefore be useful as a complementary targeted therapy against renal CSCs in the future.